1999
DOI: 10.1002/(sici)1096-9071(199912)59:4<415::aid-jmv1>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus core promoter mutations in children with multiple anti-HBe/HBeAg reactivations result in enhanced promoter activity

Abstract: Sera of two children were examined to determine whether specific hepatitis B virus (HBV) mutants may contribute to anti-hepatitis B e/hepatitis B e antigen (anti-HBe/HBeAg) reactivations during the course of chronic hepatitis B. The full-length HBV genome isolated from sera of patient 1 and the basic core promoter (BCP) from patient 2 were amplified and sequenced before and after several reactivations. The functional significance of the mutant BCP from patient 1 was studied using the luciferase assay. In both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Recent studies indicated that the A1762T ⁄ G1764A mutation correlates with development of HCC [34,35], which was in agreement with the patients who had HCC in this study. The G1764T ⁄ T1766G double mutation has been proposed to form a putative new binding site for the transcription factor hepatocyte nuclear factor 3, and is thought to be a rare mutation [36]. In contrast, this rare mutation was found in 31% of patients in an independent study [37], which was close to the present findings (29.4%).…”
supporting
confidence: 86%
“…Recent studies indicated that the A1762T ⁄ G1764A mutation correlates with development of HCC [34,35], which was in agreement with the patients who had HCC in this study. The G1764T ⁄ T1766G double mutation has been proposed to form a putative new binding site for the transcription factor hepatocyte nuclear factor 3, and is thought to be a rare mutation [36]. In contrast, this rare mutation was found in 31% of patients in an independent study [37], which was close to the present findings (29.4%).…”
supporting
confidence: 86%
“…The sequence formed from the C1766G mutation has been suggested to form a putative binding site for the transcription factor hepatocyte nuclear factor 3 (HNF3). This was supported by the fact that it has been found to give a small increase in core promoter activity, presented as evidence that variations in this part of the core promoter alter the binding of transcription proteins to HBV DNA [Gerner et al, ]. It has already been observed that these mutations are always accompanied by a G1757A mutation [Sendi et al, ], and this was confirmed by our results, but we could see an association with the C1773T mutation as well.…”
Section: Discussionsupporting
confidence: 90%
“…4). Continuing viral replication in the anti-HBe seropositive carrier is not uncommon (Gerner et al, 1999;Misawa et al, 2006;Tedder et al, 2002) and is often associated with progression to liver disease including both cirrhosis (Chu et al, 2004) and HCC (Yang et al, 2002). Two years after the loss of HBeAg, the difference in HBV DNA between the two groups in this study remained statistically significant (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…3) indicating the validity of the grouping into two phenotypes. This divergence relatively soon in the anti-HBe carrier state suggests that although the escape from down regulation generally tends to evolve with time in the anti-HBe carrier (Gerner et al, 1999;Nishizono et al, 1997;Tedder et al, 2002), there are patients in whom this escape occurs very early on and that their study might reveal how this occurs in vivo. In our study levels of HBVVL at seroconversion were significantly higher in group 1 patients (P = 0.018) where 7/11 patients showed HBeAg reversion.…”
Section: Discussionmentioning
confidence: 99%